2011
DOI: 10.4067/s0034-98872011001100015
|View full text |Cite
|
Sign up to set email alerts
|

Successful rituximab therapy in refractory autoimmune hepatitis and Evans syndrome

Abstract: A 44-year-old woman was found to have elevated aminotransferases, twice the upper limit of normal. Liver biopsy demonstrated a mixed infl ammatory process suggestive of both primary biliary cirrhosis and autoimmune hepatitis (AIH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…A middle-aged woman with AIH-PBC overlap syndrome entered remission using prednisone and azathioprine [200]. She appeared to relapse on therapy, but did not respond to intensified prednisone, azathioprine or MMF.…”
Section: Rituximabmentioning
confidence: 95%
“…A middle-aged woman with AIH-PBC overlap syndrome entered remission using prednisone and azathioprine [200]. She appeared to relapse on therapy, but did not respond to intensified prednisone, azathioprine or MMF.…”
Section: Rituximabmentioning
confidence: 95%
“…A later report of a patient with concurrent diagnoses of B cell lymphoma and steroid resistant AIH/PBC overlap syndrome showed that a total of a 12-week treatment with rituximab resulted in clinical, biochemical and histological remission of the liver disease [81]. Rituximab has also been reported as an effective treatment of AIH in patients with concomitant idiopatic thrombocytopaenic purpura [82], cryoglobulinaemic glomerulonephritis [83], or Evans syndrome [84]. In a phase 1 study, 6 patients with isolated AIH refractory to standard treatment, were treated with rituximab (1000 mg at days 1 and 15) [85].…”
Section: Rituximabmentioning
confidence: 95%
“…117,118 These presumptions have been supported by the successful treatment of autoimmune hepatitis and idiopathic thrombocytopaenic purpura 119 ; autoimmune hepatitis and cryoglobulinemic glomerulonephritis 120 ; autoimmune hepatitis and previous B cell lymphoma 121 ; and autoimmune hepatitis and Evans syndrome (autoimmune haemolytic anaemia and idiopathic thrombocytopaenic purpura). 122 A recent study has extended treatment with rituximab to patients without co-existent B-cell disease. In an abstract describing 6 patients with autoimmune hepatitis intolerant of or refractory to therapy with prednisone and azathioprine, rituximab administered intravenously (1000 mg at days 1 and 15) was associated with biochemical resolution and improvement of IgG and c-globulin levels with no serious adverse events.…”
Section: -82mentioning
confidence: 99%